GamTox: A Low-Cost Multimetric Ecotoxicity Test with Gammarus spp. for In and Ex Situ Application - Almut Gerhardt (International Journal of Zoology, 2011)
Gammarus spp. represent an important taxon in running water ecosystems concerning both structural and functional aspects. Gammarus spp. are also part of several macrozoobenthos indices for assessing biological water quality. However, in ecotoxicological water quality assessment, this taxon has been used much less than Daphnia spp. A new user-friendly and low-cost test protocol for Gammarus spp. has been developed, constituting the “ecotoxicological module ”of an integrated multimetric triad-based concept for water quality assessment. The GamTox test is based on several test parameters: behavior (especially locomotion and feeding) depicts rapid and sensitive early warning indicators, survival displays an indicator of severe acute stress, and biochemical biomarkers, esp. AChE inhibition, is a sensitive marker of neurotoxic xenobiotic stress. GamTox can be performed both in situ and ex situ, based either on visual or automatical recording.